Structural Design and Dynamics Analysis of a Lower Limb Rehabilitation Training Mechanism - Wang Yan; Li Jian (Jixie chuandong)
Aiming at the situation that there are a large number of paraplegic patients in China and there is a shortage of rehabilitation training equipment for lower limbs, a simple rehabilitation training mechanism for lower limbs is designed. The structure, driving method and length adjusting mechanism of the mechanism are introduced，its kinematics and dynamics are analyzed theoretically. By using the dynamic simulation software, the change of angular velocity and output torque of each joint in one motion period is analyzed. The flexibility analysis of the thigh and calf length adjusting mechanism is carried out, and the stress variation of the thigh and calf length adjusting mechanism is obtained in one motion period. The maximum stress is 70 MPa, which is less than the allowable stress of aluminum alloy, and the strength meets the use requirements. At last, the lower limb rehabilitation mechanism is verified by experiments. The measured output torque of hip joint and knee joint show the same trend as the simulation results, the correctness and feasibility of the simulation is proved. In the simulation, the gap and human resistance are ignored, resulting in the measured moment slightly larger than the simulation result.